KONSISTENSI PENGGUNAAN METODE PENERJEMAHAN LAFAZ RAḤMĀN DALAM “AL-QUR’AN DAN TERJEMAHANNYA EDISI PENYEMPURNAAN 2019” KARYA KEMENAG RI - Hilmi, Hafidzatul; Najib, Muhammad (STAI AL-ANWAR SARANG, 2021)
This article presents an analytical study of the consistency of the use of the translation method used by the Ministry of Religion of the Republic of Indonesia in the